Some factors affecting achievement in elementary science - Castillo, Jovito B. 1931- (s.n.], 1966)
This study determined the degree of relationship between achievement in elementary science and a group of variables such as: skill in arithmetic, skill in reading, and mental ability. The researcher constructed a test to determine whether a relationship exists between achievement in elementary science and other factors such as socio-economic status or physical health conditions. Moreover, the writer predicted achievement in elementary science on the basis of skill in arithmetic, skill in reading, and mental ability.